2014
DOI: 10.1038/srep06888
|View full text |Cite
|
Sign up to set email alerts
|

The intrinsic disorder related alloy scattering in ZrNiSn half-Heusler thermoelectric materials

Abstract: The intrinsic structural disorder dramatically affects the thermal and electronic transport in semiconductors. Although normally considered an ordered compound, the half-Heusler ZrNiSn displays many transport characteristics of a disordered alloy. Similar to the (Zr,Hf)NiSn based solid solutions, the unsubstituted ZrNiSn compound also exhibits charge transport dominated by alloy scattering, as demonstrated in this work. The unexpected charge transport, even in ZrNiSn which is normally considered fully ordered,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

33
195
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 240 publications
(231 citation statements)
references
References 50 publications
33
195
3
Order By: Relevance
“…Excess Fe may enter into the interstitial tetrahedral sites of the crystal structure to supply electrons, and make the hole concentration decrease. This phenomenon is similar to the scenario happened in another HH compound Ni 1+ y ZrSn, in which excess Ni had been proven to enter into the interstitial tetrahedral sites and generate electrons 28, 39…”
supporting
confidence: 75%
See 3 more Smart Citations
“…Excess Fe may enter into the interstitial tetrahedral sites of the crystal structure to supply electrons, and make the hole concentration decrease. This phenomenon is similar to the scenario happened in another HH compound Ni 1+ y ZrSn, in which excess Ni had been proven to enter into the interstitial tetrahedral sites and generate electrons 28, 39…”
supporting
confidence: 75%
“…In contrast, high m b * of ≈2.5 m e are found for the p‐type Fe(V,Nb)Sb and ZrCoSb‐based HH compounds 29, 30. The room temperature μ of these p‐type HH compounds is usually several times lower than that of the typical n‐type counterparts,27, 28, 29, 30 which usually means smaller l c at the optimal carrier concentration. Hence, introducing more phonon scattering centers into the p‐type HH materials may be more feasible to improve their zT s, compared with the n‐type counterparts.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the ultrahigh peak value, Nb 0.95 M 0.05 FeSb (M = Hf, Zr, Ti) system also showed remarkable enhancement in PF over a wide range of temperature in comparison with other high‐performance thermoelectric materials (see Figure 1), indicating the great potential for power generation over a wide temperature range. Furthermore, understanding the carrier scattering mechanism plays a crucial role in optimizing the electrical properties of thermoelectric materials, such as Mao et al demonstrated a significant enhancement in the mobility and PF of n‐type Mg 3.2 Sb 1.5 Bi 0.49 Te 0.01 by carefully tuning the hot pressing temperature to manipulate the variation of scattering mechanisms,61 while few studies focusing on the scattering mechanism in HH 63, 64. Therefore, further systematical investigation on the carrier scattering mechanism in the materials with ultrahigh PF is still necessary.…”
Section: Resultsmentioning
confidence: 99%